1995
DOI: 10.1051/mmm:1995133
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of the Radiolytic Transformation of Thin Films of Titanium Dioxide using EELS

Abstract: . 2014 The reduction of TiO2 (anatase) subjected to high flux electron irradiation (~ 108 A/m2) to titanium monoxide is followed using the evolution of fine structure in the electron energy loss spectrum. Changes in extended fine structure are consistent with changes in interatomic distance and the shift in d band onset clearly shows the transition from insulator to metal.Microsc. Microanal. Microstruct. ClassificationPhysics Abstracts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
3
9
1
Order By: Relevance
“…The absence of splitting has already been reported as well for amorphous, i. e. disordered, Ti02 [13] as for substoichiometric TiOx. However in the latter case a shift of the Ti L2,3 edge should be observed [14]. In the present study, no detectable shift has been found in the neighbourhood of the interface, confirming the hypothesis of the existence of a Ti02-Si02 solid solution.…”
Section: Expérimental Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The absence of splitting has already been reported as well for amorphous, i. e. disordered, Ti02 [13] as for substoichiometric TiOx. However in the latter case a shift of the Ti L2,3 edge should be observed [14]. In the present study, no detectable shift has been found in the neighbourhood of the interface, confirming the hypothesis of the existence of a Ti02-Si02 solid solution.…”
Section: Expérimental Resultssupporting
confidence: 77%
“…Simultaneously, one notices the disappearance of the splitting on Ti L2,3 and 0 K edges, as well as the decay of the extended fine structure of Ti L2,3 edge. As no shift on the Ti L3 edge position is observed, contrary to the case investigated in reference [14] where this shift was explained by a reduction of Ti02 down to TiO, it is likely that the damage observed in the present work only involves an amorphization process. As a matter of fact, Rez et In a further step, it would be necessary to investigate, within the relevant range of electron doses, how the different materials behave as a function of local thickness.…”
Section: Expérimental Resultscontrasting
confidence: 52%
“…This is mainly attributed to the presence of an amorphous layer on the top and bottom surfaces of the specimen. The observed shape is similar to those observed for amorphous titanium oxide (Berger et al ., 1987; Rez et al ., 1995).…”
Section: Resultsmentioning
confidence: 99%
“…We would like to revisit this topic with the specific focus of High resolution EELS of this transformation and general cautionary commentary on STEM work in nanostructures. If the beam is rapidly scanned over a region such as a line or square (as indicated in Fig 1), the observed spectra (Fig 2) is typical of anatase TiO 2 with the B peak split into B 1 and B 2 and B 1 showing up stronger than B 2 [2]. In Fig 2, this is only seen as the peak at the B 1 position and an asymmetry in the B peak.…”
mentioning
confidence: 87%
“…
In 1995 Peter Rez et al discussed the Radiolytic transformation of TiO 2 to TiO under high flux electron irradiation (~10 8 A/m 2 ) as observed from the fine structure changes in Electron Energy Loss Spectra (EELS) [1]. We would like to revisit this topic with the specific focus of High resolution EELS of this transformation and general cautionary commentary on STEM work in nanostructures.
…”
mentioning
confidence: 99%